(3TQM aQGFO GdCUhd GdeYQha HGdQSGFd ddCfUGQjs - (3GdfLaj, , GHf cGTa GdZWGA, Ydj Hf eMeO QVG Hf ehSi, J HYO (B1354(3g`s ((3HNW GdeDdas)
(3ChdgG (B:s
(3ChdgG(B: (3bhdg adGf YOe LhGR GdeNGdaI GdbWYjI Cj GdeNGdaI GdbWYjI ajeG fMf ajg ddYde GdELeGdj HCf jJQc GdCbd hGdCcKQ EfeG dG JLhR ef LgI chfgG eNGdaI bWYjI JaUjdjIs
(3BNQgG (B:s
(3BNQgG(B: (3dGecGf GSJUMGH faS Gdchf aj GdUdGI GdPj CKQg MQeI GdbWY HCf jbGd Efg cGf SGHbG aj GdUdGI hTc aj NQhLg efgG HhGSWI eG Tc ajs
(3GdfSNI YHGQI Yf eShOI GdeDdas
(3JHUQI GdeDda (B:s
(3PcQ GdRQcdj haGJg SfI (B1350(3g`, ZjQ Cfg cGf MjG SfI (B1354(3, hab eG PcQg eG PcQ aj fgGjI GdLRA GdYGTQ ef cJGH TQM GdcaGjIs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe, L (B5: 19s
(3eUOQ GbJfGA GdCUd (B:s
Keywords: (3CUhd Gdabgs